SiRNA cell arrays for high-content screening microscopy. (September 2004) - Erfle, Holger; Simpson, Jeremy C.; Bastiaens, Philippe I.H.; Pepperkok, Rainer
RNA interference (RNAi) is a recent advance that provides the possibility to reduce the expression of specific target genes in cultured mammalian cells with potential applications on a genome-wide scale. However, to achieve this, robust methodologies that allow automated and efficient delivery of small interfering RNAs (siRNAs) into living cultured cells and reliable quality control of siRNA function must be in place. Here we describe the production of cell arrays for reverse transfection of tissue culture cells with siRNA and plasmid DNA suitable for subsequent high-content screening microscopy applications. All the necessary transfection components are mixed prior to the robotic spotting on noncoated chambered coverglass tissue culture dishes, which are ideally suited for time-lapse microscopy applications in living cells. The addition of fibronectin to the spotting solution improves cell adherence. After cell seeding, no further cell culture manipulations, such as medium changes or the addition of 7serum, are needed. Adaptation of the cell density improves autofocus performance for high-quality data acquisition and cell recognition. The co-transfection of a nonspecific fluorescently labeled DNA oligomer with the specific siRNA helps to mark each successfully transfected cell and cell cluster. We demonstrate such an siRNA cell array in a microscope-based functional assay in living cells to determine the effect of various siRNA oligonucleotides against endogenous targets on cellular secretion.